Lenalidomide in Relapsed or Refractory Diffuse Large B‐Cell Lymphoma: Is It a Valid Treatment Option?. (5th July 2016) - Mondello, Patrizia; Steiner, Normann; Willenbacher, Wolfgang; Ferrero, Simone; Ghione, Paola; Marabese, Alessandra; Pitini, Vincenzo; Cuzzocrea, Salvatore; Mian, Michael
Abstract : Background: Despite the advent of new treatment strategies, many patients with diffuse large B‐cell lymphoma (DLBCL) relapse or die of the disease. Prospective clinical trials have demonstrated that lenalidomide is an effective and safe treatment option, especially for non‐germinal center B‐cell (non‐GCB) DLBCL. However, routine clinical data are lacking, which is why we provide the results of the so‐far largest relapsed/refractory (R/R) DLBCL real‐life analysis. Methods: We retrospectively assessed 123 R/R DLBCL patients who received either 15 or 25 mg/day of lenalidomide from January 2006 to January 2015. Results: During a median follow‐up period of 4.5 years, complete remission was achieved in 32% and a partial remission in 33% non‐GCB patients compared with 0% and 3% in the GCB group ( p < .001 and .001, respectively), with median response durations of 15 and 5 months, respectively ( p < .001). Lenalidomide at 25 mg was superior to 15 mg in terms of response (complete remission 21% and partial remission 23% vs. 0% and 8%; p = .007 and .05) and median response duration (10 vs. 4 months; p = .03). Toxicity was limited and reversible. Median progression‐free survival differed between non‐GCB and GCB patients (37 vs. 30 months; p < .001) and between the two dosages (24 vs. 34 months; p = .002). However, overall survival was similar between the subgroups (38–42 months). Conclusion: We provide evidence that lenalidomide is a valid treatment option for R/R DLBCL, with limited and reversible toxicity, and is more efficient in non‐GCB DLBCL and at higher doses. Implications for Practice: Despite the advent of new treatment strategies, many patients with diffuse large B‐cell lymphoma (DLBCL) relapse or die of the disease; hence, novel therapeutic approaches are urgently needed. This study confirms that lenalidomide is a valid and well‐tolerated treatment option for relapsed/refractory (R/R) DLBCL. Superior outcomes were observed in non‐germinal center B‐cell (GCB) DLBCL, probably because of inhibition of the nuclear factor‐κB pathway. Similarly, high drug doses resulted in greater clinical benefits. Overall, lenalidomide is a suitable therapeutic option for R/R DLBCL, especially in non‐GCB DLBCL, and 25 mg/day dosing should be preferred. Abstract : In 123 patients with relapsed/refractory diffuse large B‐cell lymphoma who received either 15 or 25 mg/day of lenalidomide, complete remission was achieved in 32% and a partial remission in 33% non‐germinal center B‐cell (non‐GCB) patients compared with 0% and 3% in the GCB group. Lenalidomide at 25 mg was superior to 15 mg in terms of response and median response duration. Toxicity was limited and reversible.